Ferredoxin and flavodoxin in eastern Antarctica pack ice - Pankowski, A; Andrew McMinn (2008)
The presence, concentration and distribution of the iron regulated proteins, ferredoxin and Xavodoxin, was investigated in pack ice oV eastern Antarctica using SDSPAGE gels. Bands corresponding to ferredoxin and/or Xavodoxin were observed in all but eight of the 102 core sections analysed. Flavodoxin was found in most of the ice samples and was strongly correlated with chlorophyll a standing stock. The widespread distribution of Xavodoxin here is not thought to indicate iron-limitation as many of the dominant species, such as Fragilariopsis cylindrus, Cylindrotheca closterium, are known to produce this protein under iron-replete conditions and thus the signiWcant correlation between Xavodoxin and biomass is likely to be the result of widespread constitutive Xavodoxin expression among the diatoms that commonly inhabit sea ice. High concentrations of ferredoxin were predominantly derived from core sections on the Xoes closest to the continent and also in the upper portion of these Xoes. There was a consistent lack of ferredoxin expression in the high biomass bottom communities. The absence of ferredoxin is likely to indicate a reduced supply of iron but the signiWcance of this reduced iron supply cannot be inferred on the basis of protein expression alone. Furthermore, in the present study the observed variability in the Xavodoxin:ferredoxin ratio may not simply reXect the iron nutritional status of the community, but probably results from changes in the abundance of species capable of expressing ferredoxin.